2022
DOI: 10.1111/coa.13928
|View full text |Cite
|
Sign up to set email alerts
|

Complication rates for paediatric tonsillectomy based on Scottish national data 2000–2018

Abstract: Tonsillectomy is the most common operation in children in the UK, with 37 000 procedures performed between 2016 and 2017 in the UK. 1 With such a common procedure, it is important to ensure parents and patients are correctly informed of the risks involved.Personal and departmental audit data are important, of course, but in order to produce reliable estimates of uncommon complications, very large data sets are required.National audits and registries have produced useful data based on large numbers of cases, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The majority of secondary PTH episodes following BiZact™ tonsillectomy in the current study were found to be minor grade A (79.4%) and grade B (9.8%) requiring observation in hospital overnight. The return to theatre rate of 0.8% for BiZact™ was similar to that reported in the UK NPTA (0.9%) 5 and in a recent Scottish study (1%) 27 and better than the 2.7% reported in the NTSRS 13 . However, a study involving 444 children with BiZact™ tonsillectomy recently reported a return to theatre rate of 2.48% which is higher than our study, but less when compared to coblation tonsillectomy at 4.7% in the same institution 15 .…”
Section: Discussionsupporting
confidence: 88%
“…The majority of secondary PTH episodes following BiZact™ tonsillectomy in the current study were found to be minor grade A (79.4%) and grade B (9.8%) requiring observation in hospital overnight. The return to theatre rate of 0.8% for BiZact™ was similar to that reported in the UK NPTA (0.9%) 5 and in a recent Scottish study (1%) 27 and better than the 2.7% reported in the NTSRS 13 . However, a study involving 444 children with BiZact™ tonsillectomy recently reported a return to theatre rate of 2.48% which is higher than our study, but less when compared to coblation tonsillectomy at 4.7% in the same institution 15 .…”
Section: Discussionsupporting
confidence: 88%